Strength and Power-Related Measures in Assessing Core Muscle Performance in Sport and Rehabilitation - Zemková, Erika (Frontiers in Physiology, 2022)
While force-velocity-power characteristics of resistance exercises, such as bench presses and squats, have been well documented, little attention has been paid to load, force and power-velocity relationships in exercises engaging core muscles. Given that power produced during lifting tasks or trunk rotations plays an important role in most sport-specific and daily life activities, its assessment should represent a crucial part of the testing battery in both athletes and general population. This scoping review aims (i) to map the literature that addresses testing methods assessing core muscle strength and stability in sport and rehabilitation, chiefly studies with particular focus on force-velocity-power characteristics of exercises involving the use of core muscles, (iii) and to identify gaps in the existing literature and propose future research on this topic. The main literature search conducted on MEDLINE, Web of Science, Scopus, PubMed and Cochrane Library databases was completed by SpringerLink, Elsevier and Google Scholar. A total of 37 articles met the inclusion criteria. Findings identified that among a variety of studies investigating the core stability and core strength in sport and rehabilitation, only few of them analyzed force–velocity–power characteristics of exercises involving the use of core muscles. Most of them evaluated maximal isometric strength and endurance of the core musculature. However, there were few studies that evaluated muscle power during lifting tasks at different loads performed either on the Smith machine or with free weights. Similarly, power and velocity in the acceleration phase of standing and seated trunk rotations with different weights were evaluated. Nevertheless, there is still a scarce research investigating the power-velocity and force-velocity relationship during exercises engaging core muscles in able-bodied and para athletes with different demands on stability and strength of the core. Therefore, more research is needed to address this gap in the literature and aim research at assessing strength and power-related measures within cross-sectional and intervention studies. A better understanding of the power-force-velocity profiles during exercises with high demands on the core musculature has implications for designing sport training and rehabilitation programs for enhancement of athlete performance and/or decrease their risk of back pain.